CONSTRAINTS ON MAGMA CHAMBER GEOMETRY AT SIERRA NEGRA VOLCANO, GALÁPAGOS ISLANDS, BASED ON INSAR OBSERVATIONS - Yun S.; Segall P.; Zebker H. (My University, 2006)
We investigate the problem of estimating magma chamber geometry using InSAR observations of Sierra Negra Volcano, Galápagos. Ascending and descending interferograms are combined to determine vertical and one horizontal component of displacement. The ratio of maximum horizontal to vertical displacement suggests a sill-like source. Spherical or stock-like bodies are inconsistent with the data. We estimate the geometry of the sill assuming a horizontal, uniformly pressurized crack with unknown periphery and depth. The sill is discretized into small elements that are either open and are subjected to the pressure boundary condition or remain closed. We find the best-fitting sill to be located beneath Sierra Negra's inner caldera at a depth of about 2 km. Using boundary element calculations we show that any magma chamber with a flat top coincident with the sill model fits the data equally well. The data are insensitive to the sides and bottom of the magma chamber. © 2005 Elsevier B.V. All rights reserved.
Keywords: BOUNDARY ELEMENT METHOD; GALÁPAGOS; GEODESY; MAGMATIC PROCESSES; MODELING; SIERRA NEGRA VOLCANO; SYNTHETIC APERTURE RADAR INTERFEROMETRY